Hyperbaric oxygenation therapy treatment option in perioperative visual loss in spine surgery - Aleixo, Catarina; Pereira, Ricardo Santos; Santos, Filipe Lima; Sousa, Henrique; Soares, José Carlos; Maia Gonçalves, João Pedro (International Journal of Research in Orthopaedics, 2021)
Perioperative vision loss (POVL) is a catastrophic complication of spine surgery and several risk factors are identified. As spine fusion surgery is rising in number, POVL incidence is increasing. Preventive strategies can decrease the risk of this complication. Prognosis depends on the level of occlusion and how quickly oxygen supply can be restored to retina. We present a 65-year-old female patient with multiple cardiovascular risk factors that who underwent lumbar fusion. Upon waking up from anesthesia, the patient reported total loss of vision in her left eye. An occlusion of the central retinal artery due to a probable embolic cause was diagnosed and the patient promptly started treatment with anti-aggregation therapy and hyperbaric oxygen therapy (HBOT) with good results. The combination of HBOT with anti-aggregation therapy may have had a synergistic effect contributing to the good outcome presented in this case and may be a good option for the treatment of this patients.